COMPARISON OF AUTOMATED BLOOD PRESSURE MEASUREMENTS WITH CONVENTIONAL READINGS IN A MUNICIPAL OUTPATIENT CLINIC. (June 2018) - Andreadis, E.; Geladari, C.
Abstract : Objective: Conventional office blood pressure (COBP) readings are compromised by artificial increases in in blood pressure (BP). Automated office blood pressure (AOBP) technique eliminates the white-coat response and sequel improves the validity of office readings. The clinical interpretation of BP readings taken in real life outside hospital clinics is not clear. Objective: To compare community AOBP with COBP readings in a public outpatient clinic. Design and method: Blood pressure (BP) was measured twice in the clinic with a validated oscillometric device, after a 5-min rest period in a sitting position (Microlife WatchBP Office, Microlife AG, Widnau, Switzerland). Consequently, all participants were measured with an Omron 907 XL to obtain AOBP readings. The patient was left alone to rest for 5 min after which the device was set to record BP at 1 min intervals. All three readings were used to determine the mean AOBP. Results: A total of 81 individuals, mean age 63.14 ± 12.32 years, 45 women were included in the analysis. The mean systolic AOBP ± SD was 133.83 ± 14.54 mmHg and the mean systolic COBP ± SD was 146.62 ± SD 20.95 mmHg, p < 0.001. The mean systolic AOBP-COBP difference was 12.79 ± 12.11 mmHg (95% confidence interval 10.11 to 15.47, p < 0.001). Furthermore, the mean diastolic AOBP was 76.93 ± 11.27 mmHg and the mean diastolic COBP was 84.99 ± 12.40 mmHg, p < 0.001 and the mean diastolic AOBP-COBP difference was 8.06 ± 7.55mmHg (95% confidence interval 6.39 to 9.73). Conclusions: AOBP readings appear to yield lower BP values compared to COBP and could be recognized as a valuable tool for hypertension diagnosis in public clinics.